THU0028 COMPARISON OF IL-17A AND TNF INDUCED CYTOKINE SECRETION BY RHEUMATOID AND PSORIATIC ARTHRITIS SYNOVIAL FIBROBLASTS AND THEIR INHIBITION BY BIOLOGICS. (June 2019) - Frommer, Klaus; Rehart, Stefan; Müller-Ladner, Ulf; Neumann, Elena
Abstract : Background: Rheumatoid arthritis (RA) and psoriatic arthritis (PsA), although similar in several respects, display clinical as well as therapeutic differences. This includes, for example, the higher effectiveness of the anti-IL17A biologic secukinumab in PsA than in RA patients. Synovial fibroblasts (SF) are one of the key effector cell types in the pathophysiology of RA and PsA. We hypothesized that RASF and PsASF respond differentially to IL-17A and its biologic secukinumab and that this might contribute to the difference seen in the therapeutic response. Objectives: To examine the effect of the two cytokines IL-17A and TNF-α on RASF in comparison to PsASF as well as the effect of their corresponding biologics. To analyze the effect of the IL-17A homolog IL-17F. Methods: SF were isolated from synovium from PsA or RA patients undergoing surgery. SF from RA and PsA patients were stimulated with recombinant IL-17A, IL-17F and TNF-α alone or with respective combinations. Dose-response curve analysis was performed with IL-17A. The biologics secukinumab and adalimumab were used to block the effects on the SF. As a measure of the proinflammatory response, secretion of the cytokine IL–6 was quantified using an immunoassay. Results: IL-6 secretion was induced by IL-17A in RASF as well as PsASF (IL-17A: 13.7-fold ↑ vs 6.9–fold ↑; n=3). Although sharing the same receptor, the IL-17A homolog IL-17F alone caused no induction of IL-6 secretion in SF. However, when combined with TNF-α, both IL-17 isoforms, IL–17A and IL-17F, increased IL-6 secretion due to a strong synergistic effect with TNF-α. RASF (n=3) responded more strongly than PsASF (n=3) to the combined stimulation (IL-17A: 544-fold ↑ vs 127-fold ↑, IL-17F: 54-fold ↑ vs 27-fold ↑). Adalimumab and secukinumab were similarly effective in abolishing the synergistic effect of IL-17A + TNF-α in RASF and PsASF. Conclusion: According to our data, the differences in the therapeutic effectiveness of the anti-IL17A biologic secukinumab cannot be attributed to differential SF responses since the response to IL-17A alone and IL-17A together with TNF–α is not stronger for PsASF than for RASF and since secukinumab was similarly effective for both SF types. Furthermore, in a proinflammatory milieu with increased TNF levels, both IL-17A and IL-17F can contribute to promoting inflammation in the pathophysiology of PsA and RA. Acknowledgement: Supported by an unrestricted educational grant from Celgene GmbH. Disclosure of Interests: Klaus Frommer: None declared, Stefan Rehart: None declared, Ulf Müller-Ladner Grant/research support from: Projekt supported by an unrestricted educational grant from Celgene GmbH., Elena Neumann: None declared